Սենմուրվը եւ սասանյան առասպելական կենդանիները հայ միջնադարյան արվեստում - Հակոբյան, Զարուհի; Միքայելյան, Լիլիթ
Cultural relations between Armenia and Iran have more than a two-thousand-year history, an important part of which make Middle ages. In the Armenian medieval art there are a number of images, compositional solutions and decorative elements derived from Iranian origins. The important ones among them are mythological animals – the senmurve, griffin and fabulous birds (ram-bird). The earliest example of the mythological animal known in Armenia and Trans-Caucasus is senmurve the image of which has been found lately on the north pilaster capital of the drum of Echmiadzin cathedral (620). The next example is set in the southern wall of Ateni Sion (maybe the 10th century), and there is a number of mythological creatures among the bas-reliefs of the church of Holy Cross in Akhtamar (915-921). Different mythological animals we can see in the faşad decoration of a number of Armenian and Georgian churches of the 10th and 11th centuries, which were built by the kings or rulers of the region. At the same time the garments of many of those kings are decorated with similar images, such as the garments of Gagik Artsruni, Davit Kuropalalates. A number of mythological animals we can also find in the miniature and wall painting of the 11th and 13th centuries.
Keywords: Հայ միջնադարյան արվեստ